MANAJEMEN MUTU TERPADU BERBASIS MAQASHID SYARIAH DI LEMBAGA PENDIDIKAN ISLAM - Abu Lubaba; Gama Pratama; Muhammad Atiq Ramadhani (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
Islamic educational institutions face mounting pressure to demonstrate quality outcomes that align with both contemporary academic standards and core Islamic values. While Total Quality Management (TQM) frameworks have been widely adopted in educational settings, their application in Islamic institutions frequently overlooks the deeper theological and philosophical foundations that distinguish Islamic education from secular counterparts. This study aims to examine the conceptual integration of TQM principles with the Maqashid Syariah framework specifically the five essential objectives of preserving religion (hifzh al-din), life (hifzh al-nafs), intellect (hifzh al-aql), lineage (hifzh al-nasl), and property (hifzh al-mal) as a holistic quality management model for Islamic educational institutions. Employing a library research methodology, data were gathered systematically from authoritative books, peer-reviewed journal articles, and relevant policy documents published within the past five years. The analysis reveals that integrating Maqashid Syariah into TQM enriches the quality management paradigm by embedding spiritual accountability and ethical governance into institutional processes. The findings further indicate that this integration produces a distinctive quality assurance framework capable of simultaneously addressing educational effectiveness and Islamic values orientation